Kajian Awal Pemanenan Siput Laut (Gastropoda) di Pantai Krakal, Yogyakarta: I. Volume Pemanenan - Zahida, Felicia; Sinulingga, Mastok B. (Universitas Atma Jaya Yogyakarta, 2004)
A preliminary study on marine snails harvest (Gastropods) has been done in Krakal beach, Yogyakarta, during October to December 2003. Krakal beach has become an underpressure habitat since tourism industry occurred all over Indonesia. Marine snails have been harvested for over two decade but there is no study regarding the effect of this activity. This study aims to elucidate the number of species harvested, the number of each species collected, juvenil and adult, the dominant species, and hypothesize the exploitation status. Fourty species were found, 32 of these population harvested were dominated by the young. Harvest volume was about 3146 per month. These results indicate an overexploitation status.